A few problems on translation during English teaching concerning agriculture - SHAN Xian-xin (浙江大学学报. 农业与生命科学版, 2000)
English-translating is the delicate point in the process of agricultural English-teaching. The author suggests more attention should be paid to the English structures and their relative translating skills. At the same time, the errors in the original articles may well be dealt with in a proper way. A comparatively complete analysis of the translating problems has been made here.